Evaluation of HZETRN on the Martian surface: Sensitivity tests and model results. (August 2017) - Slaba, Tony C.; Stoffle, Nicholas N.
Abstract: The Mars Science Laboratory Radiation Assessment Detector (MSLRAD) is providing continuous measurements of dose, dose equivalent, and particle flux on the surface of Mars. These measurements have been highly useful in validating environmental and radiation transport models that will be heavily relied upon for future deep space missions. In this work, the HZETRN code is utilized to estimate radiation quantities of interest on the Martian surface. A description of the modeling approach used with HZETRN is given along with the various input models and parameters used to define the galactic cosmic ray (GCR) environment and Martian geometry. Sensitivity tests are performed to gauge the impact of varying several input factors on quantities being compared to MSLRAD data. Results from these tests provide context for inter-code comparisons presented in a companion paper within this issue. It is found that details of the regolith and atmospheric composition have a minimal impact on surface flux, dose, and dose equivalent. Details of the density variation within the atmosphere and uncertainties associated with specifying the vertical atmospheric thickness are also found to have minimal impact. Two widely used GCR models are used as input into HZETRN and it is found that the associated surface quantities are within several percent of each other.